0
$\begingroup$

Let $G$ and $G'$ be groups and suppose $f:G\to G'$ is operation-preserving; i.e. $f(a\ast b) = f(a) \circ f(b)$ where $\ast$ is the group operation on G and $\circ$ is the group operation on $G'$.

The proposition states exactly that $f(e) = e$, but I don't think that this is true (or perhaps, I think it may lack information). It's clear that $e \in G$ and $f(e) \in G'$. However, I don't see why $e_G = e_{G'}$. I can't imagine why the identity element in G must be equal to the identity element in $G'$ if there exists an operation-preserving map between them. I imagine that $f(e_G) = e_{G'}$.

Despite my misunderstanding, I've tried $f(e_G) = f(e_G \ast e_G) = f(e_G) \circ f(e_G)$, and wanted to "add" $-f(e_G)$ to both sides, but I know that's probably incorrect (and also implies $e_G$ is an additive identity element).

$\endgroup$
  • $\begingroup$ Yes, it is true that $f(e_G) = e_{G'}$. Clearly, $e_G = e_{G'}$ is not true, because nothing is given about the groups! Similarly, $f(a^{-1}) = (f(a))^{-1}$ can also be proved in a manner similar to yours. But your proof of $f(e_G) = e_{G'}$ is not complete so finish it. $\endgroup$ – Teresa Lisbon Nov 14 '16 at 10:57
  • $\begingroup$ Unfortunately, I'm currently stuck at my equality listed in the OP. $\endgroup$ – playitright Nov 14 '16 at 11:00
  • 1
    $\begingroup$ You have $f(e_G)=f(e_G)\circ f(e_G)$. How many elements in $G'$ have the property that $g=g\circ g$? Clearly, $f(e_G)$ must be one of them. (You can't "add $-f(e_G)$", but you can ${}\circ f(e_G)^{-1}$.) $\endgroup$ – Arthur Nov 14 '16 at 11:04
  • $\begingroup$ Ah, light bulb. Thank you! $f(e_G) = e_{G'}$ is the only one because the identity element is unique. $\endgroup$ – playitright Nov 14 '16 at 11:07
2
$\begingroup$

Note that: $$ f(e_G) = f(e_G*e_G) = f(e_G)\circ f(e_G) $$ Now, multiply ($G'$ - product) on both sides by the inverse of $f(e_G)$, which exists because $G'$ is a group: $$ e_{G'} =f(e_G) \circ f(e_G)^{-1} = (f(e_G)\circ f(e_G))\circ f(e_G)^{-1} = f(e_G) $$ Which completes the proof.

For the other part, just use the concept of inverse.Note that: $$ e_{G'} = f(e_G) = f(a * a^{-1}) = f(a) \circ f(a^{-1}) $$ So, $f(a)^{-1} = f(a^{-1})$ holds, since their product is the identity.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.